Design and prototype development of credit transfer and exemption system in FIIT, UNISEL, Malaysia - Omar, Siti Fatimah; Jusoff, Kamaruzaman; Sutan Ahmad Nawi, Haslinda; Abu Hassan, Mohammad Ashri; Widyarto, Setyawan; Ahmad Shukor, Nur Syufiza (2011)
Credit transfer and credit exemption (CTCE) are one of the crucial processes in higher learning institution. Due to typically processed using manual system, it is time consuming and unorganized data filing to the applications and process of approval of applications at Universiti Industri Selangor (UNISEL). Besides, there is no standardized process flow for CTCE among all faculties. Therefore, to improve the process to be more efficient and organized, a prototype system to standardize process flow of CTCE is designed and developed. Rational Unified Process (RUP) is been used because RUP is a complete methodology and well-documented for software engineering. The solution is expected to allow online application and approval and the monitoring to the both process. It also helps in organizing record digitally and eliminates the manual paper based system. Therefore, all faculties at UNISEL must follow a standardized process flow for CTCE process.